2020
DOI: 10.14309/ajg.0000000000000597
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Comorbidities and Psychiatric Medication Use Are Highly Prevalent in Patients With Eosinophilic Esophagitis and Associate With Clinical Presentation

Abstract: OBJECTIVES: The prevalence of psychiatric disease in patients with eosinophilic esophagitis (EoE) is not fully characterized. We aimed to determine the prevalence of psychiatric disease and centrally acting medication use in a cohort of children and adults with EoE and evaluated whether psychiatric disease affects the EoE clinical presentation. METHODS: We conducted a retrospective study of newly diagnosed cases with EoE at the University of North Carol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 24 publications
4
32
1
Order By: Relevance
“…This study reinforces findings of prior studies that show psychiatric comorbidities are common in patients with EoE. 9,10 In a cohort of 883 patients with EoE, up to 1 in 3 adults and more than 1 in 7 children had psychiatric comorbidities, with anxiety being the most common diagnosis. 9 Although the study highlights potential role of anxiety and hypervigilance in symptom generation, it has significant limitations.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…This study reinforces findings of prior studies that show psychiatric comorbidities are common in patients with EoE. 9,10 In a cohort of 883 patients with EoE, up to 1 in 3 adults and more than 1 in 7 children had psychiatric comorbidities, with anxiety being the most common diagnosis. 9 Although the study highlights potential role of anxiety and hypervigilance in symptom generation, it has significant limitations.…”
supporting
confidence: 89%
“…9,10 In a cohort of 883 patients with EoE, up to 1 in 3 adults and more than 1 in 7 children had psychiatric comorbidities, with anxiety being the most common diagnosis. 9 Although the study highlights potential role of anxiety and hypervigilance in symptom generation, it has significant limitations. Questionnaires were given immediately before endoscopy, and there are no longitudinal data available to compare the effect of waiting for the procedure itself.…”
mentioning
confidence: 99%
“…Moreover, 36% of the sample scored above the 80 th percentile on the Symptom Checklist-90-Revised Global Severity Index, which measures multiple mental health domains, including anxiety, phobic anxiety, and obsessive-compulsive behaviors. 33 A retrospective review in the same year found identical rates of anxiety as measured by the HADS (23%) in 883 patients with EoE, 34 suggesting anxiety is an important mental health consideration in this population. Comparatively, a 2019 retrospective chart review identified only 9.3% of 34 patients had an International Classification of Diseases, Ninth Revision 35 or International Classification of Diseases, Tenth Revision 36 diagnosis of an anxiety disorder.…”
Section: Discussionmentioning
confidence: 97%
“…Multiple aspects such as disturbing symptoms of dysphagia and food impaction and the need for life‐long treatment are associated with impaired HRQOL 5‐7 . A recent medical record review observed a prevalence of psychiatric health comorbidities in almost one‐third of EoE patients, in which older age, female gender, and longer symptom duration were found to be associated with the presence of a mental health disorder 8 . Current research has mainly focused on increased risk of developing anxiety and depressive symptoms, measured within the construct of disease specific HRQOL (EoE‐QOL‐A) 7,9,10 .…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 , 7 A recent medical record review observed a prevalence of psychiatric health comorbidities in almost one‐third of EoE patients, in which older age, female gender, and longer symptom duration were found to be associated with the presence of a mental health disorder. 8 Current research has mainly focused on increased risk of developing anxiety and depressive symptoms, measured within the construct of disease specific HRQOL (EoE‐QOL‐A). 7 , 9 , 10 This validated measure consists of 5 domains that evaluates important disease‐related topics (e.g., issues related to having a chronic disease or swallowing anxiety) and has been widely used in the EoE‐research field.…”
Section: Introductionmentioning
confidence: 99%